2021
DOI: 10.3390/ijerph18168501
|View full text |Cite
|
Sign up to set email alerts
|

Reference Data for Fat Mass and Fat-Free Mass Measured by Bioelectrical Impedance in Croatian Youth

Abstract: Fat mass and fat-free mass have become useful clinical indices in determining healthy growth and physical development during critical periods of childhood and adolescence; however, despite a wide range of nutritional surveillance its study is limited by a lack of reference data. The purpose of this study was to establish sex-specific and age-specific standards for fat mass and fat-free mass in a large sample of Croatian children and adolescents. In this cross-sectional study, we collected data from 12,678 part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
(60 reference statements)
1
2
0
Order By: Relevance
“…When anthropometric indices of boys were compared to those of girls, the majority of indices for girls were significantly higher than those for boys, with the exception of FFM, MM, and SMM percentages, which were significantly higher in boys. The current results were in agreement with a previous study conducted in Croatia among 1149 boys and girls that compared body composition between genders, which showed that girls had significantly higher FM, FM, and FMI than boys and significantly lower FFM than boys [ 38 ]. Moreover, a study showed that the percentage of FM was higher in Czech girls than boys, and FFM (kg) and SMM (kg) were higher in boys than girls [ 39 ].…”
Section: Discussionsupporting
confidence: 93%
“…When anthropometric indices of boys were compared to those of girls, the majority of indices for girls were significantly higher than those for boys, with the exception of FFM, MM, and SMM percentages, which were significantly higher in boys. The current results were in agreement with a previous study conducted in Croatia among 1149 boys and girls that compared body composition between genders, which showed that girls had significantly higher FM, FM, and FMI than boys and significantly lower FFM than boys [ 38 ]. Moreover, a study showed that the percentage of FM was higher in Czech girls than boys, and FFM (kg) and SMM (kg) were higher in boys than girls [ 39 ].…”
Section: Discussionsupporting
confidence: 93%
“…Fat free mass is associated with a good physical and cardiorespiratory fitness as an important predictor of the current and future health. Higher levels of fat free mass may increase the sensitivity to insulin, which contributes to the uptake of glucose by muscles thus preventing excessive glucose spikes after meals (Ciardullo et al, 2023;Henriksson et al, 2016;Kasović et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Sex‐differences that are consistent across human populations, but with varying proportions of FMI and FFMI across ethnic groups (Hull et al, 2011; Jin et al, 2019; Xiong et al, 2012) and even geographical regions within a country (Jin et al, 2019). Thus, there have been proposed sex‐ and age‐specific references values for different population groups (Kasović et al, 2021; Kelly et al, 2009; Lu et al, 2012; Schutz et al, 2002; Wells, 2014). It is hypothesized that genetic factors and environmental conditions such as periods of deprivation (famines) (Ravelli et al, 1976; Ravelli et al, 1999; Stein et al, 2007; Zhou et al, 2018) and the obesogenic environment (diets high in calories and sedentary behaviors) might be the mechanisms underlying the observed variability in FMI and FFMI among populations (Wells, 2006, 2007).…”
Section: Discussionmentioning
confidence: 99%